The Layout of the Song of Moses (Deut 32) in Masoretic Manuscripts and Biblia Hebraica Quinta - Lind, Sarah (2013)
Illustrating with the Song of Moses, Dominique Barthélemy argued the importance, in the preparation of a critical edition, of distinguishing the work of the copyist from that of the Masorete in Masoretic manuscripts. This article reviews the argument and considers its application in the layout of the Song in Biblia Hebraica Quinta.
Keywords: Aleppo Codex; Biblia Hebraica Quinta; Deuteronomy 32; Leningrad B19A; Masoretic manuscripts